Slavery, Statehood and Economic Development in Sub-Saharan Africa - Dirk Bezemer; Jutta Bolt; Robert Lenzink (African Economic History Network (AEHN), 2012)
This paper addresses the long-term impact of Sub-Saharan Africa's indigenous systems of slavery on its political and economic development, based on an analytical survey of the literature and data collected from anthropological records. We develop a theory to account for this based on the framework proposed by North et al. (2009), where indigenous slavery may have impeded the transition from a 'limited access state' centred around personal relations to an 'open access state' based on impersonal rule of law and widely shared access to public and private organisations. In a quantitative analysis we find that indigenous slavery is robustly and negatively associated with the quality of governance and with current income levels.
Keywords: N17; N27; N37; N47; N57; 330; Africa; Slavery; States; colonialism; economic development